Поховальний обряд населення Дніпровського Лісостепового Лівобережжя ранньоскіфського часу: варіант аналізу - Гречко, Д.С. (Археологія і давня історія України, 2018)
Стаття присвячена результатам кластерного аналізу поховань ранньоскіфського часу Дніпровського Лісостепвого Лівобережжя. Виділяються кластери та групи, які мають локальні та етнокультурні риси. Аналізуються поховальні споруди, їх орієнтування та поховальний інвентар. The article is devoted to the results of a cluster analysis of the burials of the Early Scythian time of the Dnieper forest-steppe Left Bank. Clusters and groups are distinguished which have local and ethno-cultural characteristics. The analysis made it possible to distinguish two large blocks of clusters: the «Posulian» and «Vorklinsky» clusters, which confirmed the previous conclusions of the researchers. An analysis of the orientation of the burials has shown that the population of the Dnieper forest-steppe Left Bank of the Early Scythian time was dominated by the idea of placing the world of the dead in the south, both among farmers and nomads. Deviation from the basic orientation could be seasonal, or associated with the direction of the land of ancestors, or an important landmark (Greater Skorobir for the Belsk necropolis). A necropolis is located in the village. Kupewaha, which allows one to assume that it belongs to a fairly separate group of nomads. In separate burial grounds there were recorded graves which belonged to different clusters. Burials of Vorskla’s ordinary farmers were represented by clusters 6, 8, 10, and burials, most likely, nomads — cluster 9 and groups 11B and 11B. Clusters 5, 7, 12 have an indeterminate nature. The burial grounds can be conditionally divided into necropolises of the local population, nomads and mixed ones.